Shearforce positioning of nanoprobe electrode arrays for scanning electrochemical microscopy experiments. (10th October 2015) - Adam, Catherine; Kanoufi, Frédéric; Sojic, Neso; Etienne, Mathieu
Graphical abstract: Highlights: Nanofiber arrays were positioned at solid surfaces with shearforce detection Nanoprobe electrode array fabrication by metal deposition and controlled insulation SECM experiments with a nanoprobe electrode array have been performed Modelling of the transition between individual nanoelectrode and collective behavior Nanotips acted as partial individual nano-antennas for positive feedback current Abstract: Shearforce detection was applied to the controlled positioning of nanotip arrays at air/solid and liquid/solid interfaces in scanning electrochemical microscopy (SECM). The arrays were fabricated by wet chemical etching of ordered optical fiber bundles. The shearforce detection have been performed with a non-optical detection setup between 70 and 170 kHz. The hydrodynamic nature of the shearforce interaction led to approach curves with length varying from few μm to more than 80 μm, essentially controlled by the working frequency (resonance frequency), the nature of the medium (air, water, electrophoretic paint solution) and the surface state of the fiber bundle (cleaved or etched). This interface sensitive signal was applied to the positioning of the nanotip array in a 1 μm PDMS film before the electrophoretic deposition of an insulating paint. The resulting nanoprobe electrode array, displaying nanotip electrodes individually insulated, has been characterized by cyclic voltammetry and SECM feedback curves. These results are discussed versus numerical simulations. They demonstrate that, except when in vicinity of a conductive substrate that may reveal the nanotip structure, the electrochemical behavior of the nanotip array is dictated by its micrometer dimension (the fiber bundle). In turn, they confirm the potential of shearforce detection for precise control over the array positioning.